The effects of dietary lipid levels on performance and heat‐shock protein response of juvenile white seabass, Atractoscion nobilis. (8th June 2012) - Jirsa, D.; Deng, D.‐F.; Davis, D.A.; Wang, W.‐F.; Hung, S.S.O.; Drawbridge, M.
Abstract A feeding trial was conducted to study the effect of dietary lipid on growth performance and heat‐shock protein (HSP70 and HSP60) response of white seabass (WSB), Atractoscion nobilis. Five diets were formulated to contain 440 g kg−1 protein from 300 g kg−1 fish meal, 240 g kg−1 soybean meal and 100 g kg−1 soy protein concentrate with different levels of lipid: 100, 120, 140, 160 or 180 g kg−1. At the end of the trial, heat shock response based on HSP70 and HSP60 was measured in liver and white muscle from fish at ambient temperature and temperature shock conditions. Final weight and percent gain were significantly higher for fish fed the 100 g kg−1 lipid diet than for fish fed the rest of the diets (P ≤ 0.05). Feed conversion ratio was lowest for fish fed the 100 g kg−1 lipid diet. The HSP70 and HSP60 responses were positively correlated to dietary lipid levels following temperature shock. At ambient temperature, HSP60 and HSP70 responses in muscle and HSP60 response in liver increased with dietary lipid level. Temperature shock significantly increased the HSP response of fish in all treatments. Results of this study demonstrated that a moderate (110–120 g kg−1) level of dietary lipids would be recommended for production diets but a higher dietary lipid level may be required for optimal stress tolerance.